Regulatory Disharmony and Local Government Roles in the Planned Development of the Barru Special Economic Zone: An Economic Law Perspective - Hilmiah; Ilham Nugraha; Muhammad Fitratallah Dahlan (Constitutional Law Review, 2026)
This study analyzes regulatory disharmony in the planned development of the Barru Special Economic Zone (SEZ) and its implications for the role of the Barru Regency Government as regulator, facilitator, and accelerator of area-based development. It employs normative legal research supported by limited empirical data obtained from legislation, scholarly literature, regional planning documents, and an interview with a key informant. The findings show that regulatory disharmony emerges in three aspects: authority, licensing, and financing. In terms of authority, the operational boundaries among central and regional governments, the SEZ administrator, and the management entity remain unclear. In licensing, the relationship between the SEZ administrator, the regional one-stop investment service agency, and the Online Single Submission system has not been operationally integrated. In financing, the allocation of responsibilities among the state budget, regional budget, regional-owned enterprise, management entity, and private investment remains uncertain. These conditions weaken local government roles in land preparation, investment services, and development acceleration. Regulatory harmonization is therefore required to ensure legal certainty, reduce transaction costs, and strengthen effective regional autonomy.